Conversion of α‐hydroxy(2, 4, 6‐trimethylbenzyl)diphenylphosphine oxide to TPO: oxidation vs decomposition. (25th November 2020) - Zhang, Jian-Qiu; Zhao, Jingzhuo; Li, Chunya; Ye, Jingjing; Han, Li-Biao
Abstract: This study details the oxidation of α-hydroxy(2, 4, 6-trimethylbenzyl)diphenylphosphine oxide (α-HDPO) to diphenyl(2, 4, 6-trimethylbenzoyl)phosphine oxide (TPO) by choosing the proper MnO2 as oxidant. In addition, the equilibrium of α-HDPO and 2, 4, 6-trimethylbenzaldehyde (MesCHO) was discussed. Graphical Abstract: